Animal tracking meets migration genomics: transcriptomic analysis of a partially migratory bird species. Issue 12 (20th April 2017) - Franchini, Paolo; Irisarri, Iker; Fudickar, Adam; Schmidt, Andreas; Meyer, Axel; Wikelski, Martin; Partecke, Jesko
Abstract: Seasonal migration is a widespread phenomenon, which is found in many different lineages of animals. This spectacular behaviour allows animals to avoid seasonally adverse environmental conditions to exploit more favourable habitats. Migration has been intensively studied in birds, which display astonishing variation in migration strategies, thus providing a powerful system for studying the ecological and evolutionary processes that shape migratory behaviour. Despite intensive research, the genetic basis of migration remains largely unknown. Here, we used state‐of‐the‐art radio‐tracking technology to characterize the migratory behaviour of a partially migratory population of European blackbirds ( Turdus merula ) in southern Germany. We compared gene expression of resident and migrant individuals using high‐throughput transcriptomics in blood samples. Analyses of sequence variation revealed a nonsignificant genetic structure between blackbirds differing by their migratory phenotype. We detected only four differentially expressed genes between migrants and residents, which might be associated with hyperphagia, moulting and enhanced DNA replication and transcription. The most pronounced changes in gene expression occurred between migratory birds depending on when, in relation to their date of departure, blood was collected. Overall, the differentially expressed genes detected in this analysis may play crucial roles in determining the decision to migrate, or in controlling the physiological processes required for the onset of migration. These results provide new insights into, and testable hypotheses for, the molecular mechanisms controlling the migratory phenotype and its underlying physiological mechanisms in blackbirds and other migratory bird species.